PENGARUH MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA(Lactuca sativa L.): Abstrak, Pendahuluan, Hasil pembahasan, Kesimpulan - Febri Nanda; Priyono Priyono; Siswadi Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2023)
Research on "The Effect of Manure Types on Growth and Yield of Lettuce (Lactuca sativa L.)" was carried out from 1 August to 4 September 2022 in Blimbing Village, Purwantoro District, Wonogiri Regency, with brown latosol soil type and an altitude of 296 meters above sea level. This study aims to determine the effect of the application of various types of manure on plant growth and yield, as well as to determine the type of fertilizer that gives the highest yield on green lettuce (Lactuca sativa L). This study used a completely randomized design (CRD) with a single factor, namely the type of fertilizer. The treatments in this study were without manure (K), chicken manure 16.98 grams/plant (A1), chicken manure 33.96 grams/plant (A2), chicken manure 50.94 grams/plant, (A3), cow manure 5.65 grams/plant (S1), cow manure 11.30 grams/plant (S2), cow manure 16.95 grams/plant (S3), goat manure 11.30 grams / plant (G1), goat manure 22.60 gram / plant (G2) and goat manure 33.90 gram / plant (G3). Each treatment was repeated 3 times, so there were 30 polybags with 2 plants per polybag. Data were analyzed using Analysis of Variety, followed by Duncan (DMRT) at 5% level. The results showed that the different types of manure treatment affected plant height, leaf length, leaf width, root weight and plant fresh weight (Lactuca sativa L.). Treatment of cow manure 11.30 gram/plant (S2) gave the highest results in the parameters of observation of plant height, number of leaves, and root weight with an average value of 17.97 cm, 13.7 da, 5.18 gram respectively. The highest leaf length observation parameter was produced by the chicken manure treatment of 33.96 grams/plant (A2) with an average of 20.10 cm. The goat manure treatment of 11.30 grams/plant (G1) resulted in the highest average leaf width with a value of 13.62 cm. While the cow manure treatment of 16.95 grams/plant (S3) gave the highest mean value in the parameters of plant fresh weight observation.